Acute Molecular Changes in Synovial Fluid Following Human Knee Injury: Association With Early Clinical Outcomes. Issue 9 (September 2016) - Watt, Fiona E.; Paterson, Erin; Freidin, Andrew; Kenny, Mark; Judge, Andrew; Saklatvala, Jeremy; Williams, Andy; Vincent, Tonia L.
Abstract : Objective: To investigate whether molecules found to be up‐regulated within hours of surgical joint destabilization in the mouse are also elevated in the analogous human setting of acute knee injury, how this molecular response varies between individuals, and whether it is related to patient‐reported outcomes in the 3 months after injury. Methods: Seven candidate molecules were analyzed in blood and synovial fluid (SF) from 150 participants with recent structural knee injury at baseline (<8 weeks from injury) and in blood at 14 days and 3 months following baseline. Knee Injury and Osteoarthritis Outcome Score 4 (KOOS4 ) was obtained at baseline and 3 months. Patient and control samples were compared using Meso Scale Discovery platform assays or enzyme‐linked immunosorbent assay. Results: Six of the 7 molecules were significantly elevated in human SF immediately after injury: interleukin‐6 (IL‐6), monocyte chemotactic protein 1, matrix metalloproteinase 3 (MMP‐3), tissue inhibitor of metalloproteinases 1 (TIMP‐1), activin A, and tumor necrosis factor–stimulated gene 6 (TSG‐6). There was low‐to‐moderate correlation with blood measurements. Three of the 6 molecules were significantly associated with baseline KOOS4 (those with higher SF IL‐6, TIMP‐1, or TSG‐6 had lower KOOS4 ). These 3 molecules, MMP‐3, and activin A were all significantly associated with greater improvement in KOOS4 over 3 months, after adjustment for other relevant factors. Of these, IL‐6 alone significantly accounted for the molecular contribution to baseline KOOS4 and change in KOOS4 over 3 months. Conclusion: Our findings validate relevant human biomarkers of tissue injury identified in a mouse model. Analysis of SF rather than blood more accurately reflects this response. The response is associated with patient‐reported outcomes over this early period, with SF IL‐6 acting as a single representative marker. Longitudinal outcomes will determine if these molecules are biomarkers of subsequent disease risk.